2014
DOI: 10.1128/aac.01813-13
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Antibiotic Use in France between 2000 and 2010: after the Nationwide Campaign, It Is Time To Focus on the Elderly

Abstract: .8%]; P < 0.001) and then stabilized except for individuals >60 years of age, for whom prescriptions reached the precampaign level. During the warm periods from April to September, no significant differences were estimated compared to the baseline level for the entire series, but seniors had an increasing trend that became significant as of 2005, reaching ؉21% (95% CI, ؉12.9 to ؉29.6%) in 2009 (P < 0.0001). These results highlight the need for a better understanding of antibiotic use by the elderly, requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…The significant association of BSI with STC 131 and A/B1 isolates and recent antibiotic treatment suggested that prior exposure of the gut to antibiotics might have led to long-lasting, strong colonization by these isolates, this process being favored by the high frequency of antibiotic resistance genes in their genomes. Recent reports concerning antibiotic consumption (Bernier et al, 2014 ; http://www.cclin-arlin.fr , 2014) 1 have described an increase in the use of antibiotics by the elderly over the study period. As data from our region were included in these studies, these trends toward an increase may apply to our region.…”
Section: Discussionmentioning
confidence: 98%
“…The significant association of BSI with STC 131 and A/B1 isolates and recent antibiotic treatment suggested that prior exposure of the gut to antibiotics might have led to long-lasting, strong colonization by these isolates, this process being favored by the high frequency of antibiotic resistance genes in their genomes. Recent reports concerning antibiotic consumption (Bernier et al, 2014 ; http://www.cclin-arlin.fr , 2014) 1 have described an increase in the use of antibiotics by the elderly over the study period. As data from our region were included in these studies, these trends toward an increase may apply to our region.…”
Section: Discussionmentioning
confidence: 98%
“…Examples from Belgium and France have shown that national campaigns may reduce overall antibiotic consumption, but have difficulty sustaining these successes over time 53 54. Experiences from other public health campaigns show that repeated exposure of the targeted public over long periods of time is often necessary to exert a sustained effect 47 55.…”
Section: Discussionmentioning
confidence: 99%
“…As for other high-income countries that introduced PCV13 [6, 7, 2325], in France, serotype 3 remained among the most frequent in older adults 4 years after PCV13 introduction, probably because of the absence of herd protection for this penicillin-susceptible serotype, which is rare in young children more frequently exposed to antibiotic consumption [26]. A recent study of the impact of PCV13 on PM cases in US children 3 years following vaccine introduction revealed that PM case numbers remain unchanged in the study sample and serotype 19A continued to be the most common serotype [27].…”
Section: Discussionmentioning
confidence: 99%